Absence of Malaria-Associated Coagulopathy in Asymptomatic Plasmodium falciparum Infection: Results From a Cross-sectional Study in the Ashanti Region, Ghana. (18th February 2023) - Rolling, Christina Charlotte; Phillips, Richard O; Abass, Kabiru Mohammed; Ken Adu Poku, Joseph; Osei-Mireku, Samuel; Osei-Wusu, Bright; Thompson, William; Vinnemeier, Christof D; Huebl, Lena; Langer, Florian; Francke, Paul; Kuta, Piotr; et al.
Abstract: Background: Coagulopathy is common in acute symptomatic Plasmodium falciparum malaria, and the degree of coagulation abnormality correlates with parasitemia and disease severity. Chronic asymptomatic malaria has been associated with increased morbidity. However, the role of coagulation activation in asymptomatic, semi-immune individuals remains unclear. This study investigates the potential effect of asymptomatic P falciparum infection on coagulation activation in semi-immune Ghanaian adults. Methods: Blood from asymptomatic Ghanaian adults with P falciparum blood stage infection detectable by polymerase chain reaction (PCR) or by both PCR and rapid diagnostic test and from noninfected individuals, was investigated. Markers of coagulation activation including global coagulation tests, D-dimer, antithrombin III, fibrinogen, and von Willebrand factor antigen were tested. Furthermore, blood count, inflammation markers, and liver and kidney function tests were assessed. Results: Acquired coagulopathy was not found in asymptomatic P falciparum infection. Asymptomatic malaria was associated with significantly lower platelet counts. Systemic inflammation markers and liver and kidney function tests were not altered compared to noninfected controls. Conclusions: There is no laboratory evidence for acquired coagulopathy in adults with asymptomatic P falciparum malaria in highly endemic regions. Lack of laboratory evidence for systemic inflammation and liver and kidney dysfunction indicates that asymptomatic malaria may not be associated with significant morbidity. Abstract : No laboratory evidence for acquired coagulopathy, systemic inflammation, or liver or kidney dysfunction was found in adults with asymptomatic Plasmodium falciparum infection in highly endemic regions in Ghana.